Penentuan arah mata angin di kecamatan pulau sembilan kabupaten Sinjai Perspektif Ilmu falak - ajman, muhammad; Rahmatiah,HL; Musyfikah (HISABUNA: Jurnal Ilmu Falak, 2022)
The directions of the Winds used by the people of Pulau Sembilan are guided by the sun, clouds, and stars. This study aims to determine the method of determining the cardinal directions used by the community in Pulau Sembilan District, Sinjai Regency and how to determine the cardinal directions in Pulau Sembilan District, Sinjai Regency, from the perspective of astronomy. The type of research used in this research is field research. This research uses a normative approach (syar’i) and a sociological approach. Sources of data in this study consisted of primary and secondary data. Data processing and analysis techniques were carried out in three stages, including data reduction, data presentation and drawing verification or conclusions. The method of determining the cardinal directions used by the people of Pulau Sembilan is guided by the sun, clouds, and stars. At night they use the stars for directions while during the day they use the sun and clouds. Determination of the cardinal directions that grow and develop in the community on the island of Sembilan include: Bintoeng Sulo Bawie (East), Bintoeng Balue (South), Bintoeng Lamburue (North), Bintoeng Worongporongnge (North), Bintoeng Tanra Bajoe (East) and Bintoeng Naga ( South). In astronomy, the constellations that are often used to determine the direction of the wind are Bintoeng Sulo Bawie and Bintoeng Tanra Bajoe to determine the east direction, Bintoeng Balue and Bintoeng Naga to determine the south direction, Bintoeng Lamburue and Bintoeng Worongporongnge determine the north direction. It is also hoped that astronomy students will always hold discussion forums in exploring local cultural values ​​regarding determining the direction of the wind which can also be associated with determining the direction of the Qibla.